Occurrence and Histopathological Patterns of Ovarian Tumours in a Tertiary Hospital (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Background: Ovarian tumours are common problem in gynaecology and have varied clinical presentation and histopathological appearances.Objectives: This study was undertaken to find out the occurrence and different histopathological types of the tumours originating from the ovaries.Methods: A retrospective study was carried out in the Department of Obstetrics and Gynaecology and Department of Pathology, Sir Salimullah Medical College and Mitford Hospital, Dhaka, between May 2010 and December 2014. Five hundred forty seven (547) cases of ovarian tumours were studied in respect to their histopathological appearance.Results: Out of total gynaecological admission of 5633 patients during the study period, 613 patients admitted with a clinical diagnosis of ovarian tumours: so, the occurrence was 10.9%. Out of 613 patients 547 did histopathology in the department of pathology of our institution. Of the 547 cases, majority were benign (n=379, 69.3%); followed by malignant (n=38, 7%); borderline (n=4, 0.7%); and others (n=126, 23%). Most commonly occurring benign ovarian tumours were serous cystadenoma (115; 30.3%); mature cystic teratoma (76; 20.1%) and mucinous cyst adenoma (66;17.4%). Common malignant tumours were serous cyst adenocarcinoma (21; 55.3%); mucinous cystadenocarcinoma (5; 13.2%) and dysgerminoma(4; 10.5%).Conclusion: Nine out of ten ovarian tumours were nonmalignant. Epithelial tumours were most common among both benign and malignant ovarian tumours. Overall, most common was serous cyst adenoma in benign group and serous cyst adenocarcinoma in malignant group.Bangladesh J Obstet Gynaecol, 2017; Vol. 32(1): 5-9